Heterogeneous Dynamics of Polymer Melts Exerted by Chain Loops Anchored on the Substrate Insights from Molecular Dynamics Simulation - Gao, Ke (Langmuir : the ACS journal of surfaces and colloids, 2021)
Understanding polymer-substrate interfacial dynamics at the molecular level is crucial for tailoring the properties of polymer ultrathin films (PUFs). Herein, through coarse-grained molecular dynamics simulation, the effect of length (Nloop) and rigidity (Kloop) of loop chains on the dynamics of linear chains is systematically explored, in which the loop chains are adsorbed on a solid substrate and the linear chains are covered on the loop chains. It is found that there is an optimal Kloop, which strongly confines the motion of the linear chains. Meanwhile, compared to increasing the rigidity of the loop chains, increasing the length of the loop chains can more effectively confine the motion of the linear chains. More interestingly, we observe that the mismatch of the length (ΔN) and rigidity (ΔK) between the loop and linear chains leads to dynamic asymmetry (ΔDc). The relationship between the ΔN, ΔK, and ΔDc are found to follow the mathematical expression of ΔDc ∼ (ΔN)α(ΔK)β, in which the values of α and β are around 4.58 and 0.83, separately. Remarkably, using the Gaussian process regression model, we construct a master curve of diffusion coefficient on the segmental and chain length scales of the linear chains as a function of Nloop and Kloop, which is further validated by our simulated prediction. In general, this work provides a fundamental understanding of polymer interfacial dynamics at the molecular level, enlightening some rational principles for manipulating the physical properties of PUFs